2021
DOI: 10.3389/fped.2021.609057
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Obesity and Lower Urinary Tract Symptoms Among Children and Adolescents: A Community-Based Study

Abstract: Introduction: Obesity is associated with lower urinary tract symptoms (LUTSs) and dysfunction in adults while its impact on children and adolescents remains unknown. This study aimed to explore the impact of obesity on LUTSs among children and adolescents through a large-scale community-based study.Methods: From July 2004 to April 2017, children and adolescents aged 5–15 years-old in Xin-Dian District, New Taipei City were invited to participate in our study. The exclusion criteria were a history of congenital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Regarding the relation of obesity and primary NE, the previous studies revealed conflicting results. Although Ma et al 7 and Karaci 22 found the association between obesity and primary NE, we did not found the significant relation about this issue that was similar to Wang et al 23 reported.…”
Section: Discussionmentioning
confidence: 74%
“…Regarding the relation of obesity and primary NE, the previous studies revealed conflicting results. Although Ma et al 7 and Karaci 22 found the association between obesity and primary NE, we did not found the significant relation about this issue that was similar to Wang et al 23 reported.…”
Section: Discussionmentioning
confidence: 74%
“…Although the relationship between obesity and disease is not clear, it is considered that the negative effects on bladder functions and the pressure on the pelvic organs due to changes in body structure are responsible 22 . The risk of urgency was higher in obese children than in non-obese children 23 .…”
Section: Discussionmentioning
confidence: 78%